Quantity Adjustments in Candidate Countries Regional Labour Markets - Peter Huber (European Regional Science Association (ERSA), 2003)
This paper analyses the evolution of regional unemployment rates, wages, participation rates, migration and employment of seven candidate countries in the 1990's and compares their regional labour market adjustment to a set of EU member states. I find that persistence in relative regional participation rates is larger and in region relative employment growth is larger than in the EU. Furthermore among the first round candidate countries persistence in relative regional unemployment rates is substantially lower than in the EU and wages react slightly more strongly to regional labour market conditions. Finally, the evidence presented in this paper suggests substantial heterogeneity in labour market dynamics among both first and second round candidate countries.
Keywords: 330